Vilas, parques, bairros e terreiros: novos patrimônios na cena das políticas culturais em São Paulo e São Luis - Corrêa, Alexandre Fernandes (2001)
This thesis discusses some aspects regarding the protection of the cultural heritage in São Paulo (Bird/Monumenta) and São Luís (Unesco/97), as well reflections about the approach to the ethnographic heritage. This text discuss yet the GTPI-MinC work proposition relative the juridical concept registro : a new form by inscription of the Brazilian immaterial cultural heritage. In short, I propose a bio-culture re-integration, in which the mankind, the life and every beings are situated in a same level the memorial action. Through a meta-ethnilogical point of view, I desire to aim a fundamental anthropology. In this work serve as a base the Marcel Mauss s expression: Il faut recomposer le tout!